Diet modelling: How it can inform the development of dietary recommendations and public health policy. Issue 1 (March 2014) - Buttriss, J. L.; Briend, A.; Darmon, N.; Ferguson, E. L.; Maillot, M.; Lluch, A.
Summary With the global population expected to increase to 9 billion by 2050 coupled with concerns about food security in relation to climate change and increasing prosperity in many parts of the world causing desire for a less monotonous diet, efficient use of resources such as food becomes ever more important. While the prevalence of obesity is a cause for concern in many parts of the world, many people still go to bed hungry, and in many communities, obesity co‐exists with poor diet quality. The result is a series of complex and challenging nutrition problems, such as the access to nutritionally adequate and affordable diets and the development of dietary recommendations. Diet modelling is a useful tool to help identify solutions to such complex questions and this paper summarises a session on this topic at the International Congress of Nutrition that took place in September 2013.